Venus of Khala-Kanti - Kingué, Angèle, 1958- (Griot Project book series., 2015)
The story of Venus of Khala-Kanti unfolds in the ancient forests of an imaginary West African village. The story is at once a straightforward narrative of human courage and an allegory for the amputation of a continent and its peoples. The tale is, above all, the story of hope, recovery and rediscovery. The vitality and reclamation of the characters is accomplished through an indomitable and lyrical animation of the natural world in concert with human kindness, empathy and zest for life.